THE EFFECT OF JOB INSECURITY ON PERFORMANCE THROUGH JOB STRESS AS INTERVENING VARIABLE FOR RETAIL STORE EMPLOYEES IN SURABAYA - Natalia, Fransisca; Lindawati, Tuty; Pradana, Dominicus Wahyu (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2022)
This study aims to analyze and test the influence of job insecurity with job stress as mediation to performance in employees of convenience stores (retail) in Surabaya. The sample was 105 respondents. The data collection tool used is a questionnaire with a copying method using convenience sampling. Hypothesis analysis and testing techniques using PLS-based SEM (Structural Equation Modeling) (Partial Least Square) are processed using the SmartPLS 3.0 program. This study showed that job insecurity has a negative and significant effect on job stress, job stress has a positive and significant effect on performance, job insecurity has no effect on performance, and job insecurity has an indirect effect negatively and significantly on performance